The Reification Concept in Contemporary Theater - Isa, Yahya (Jordan Journal of Social Sciences, 2020)
The purpose of this research is to identify the Reification concept in philisophical thought and in contemporary theater; as this concept means: the transformation of relations between humans into what is more like relations between subjects, and is to turn out to be non-personal relationships. The concept will be monitored through a play called “The Hat and the Prophet” written by the Palestinian “Ghassan Kanafani”. The researcher intended to observe the characters and the context of the play and monitor its reflection on humans. This study will be beneficial for Researchers, Directors, Authors, and Critics, as well as theater Academic institutions.